Molecular study and analysis of organic compounds for high-performance solar cell applications - El Mhamedi Imane; El Malki Zakaria (E3S Web of Conferences)
In this study, we used time-dependent density functional theory DFT/TD-DFT methods in its B3LYP/6-311G(d,p) formalism to model and analyze various properties of conjugated organic compounds. More specifically, the targeted systems consist of a D donor unit (carbazole), an A acceptor unit (benzothiadiazole) and various donor motifs. Quantum simulation via DFT/TD-DFT has enabled us to assess their fundamental electronic structures, boundary energy levels and optical absorption properties.Using AMPS1D software, we carried out an in-depth analysis of the photovoltaic properties of six compounds associated with the PCBM acceptor. These compounds were classified into two distinct categories. In the initial section, we evaluated the energy conversion efficiency of compounds, with performances between 7% to 11%. The second section presented the addition of a PEDOT layer between the active layer and the anode, which significantly improved photovoltaic performance, reaching a maximum efficiency of 15%. These results underline the positive impact of PEDOT addition on photovoltaic conversion and its potential for organic solar cells. In conclusion, our results indicate that these compounds represent promising candidates for future applications.